Multi-attribute Seismic application for Modeling Static Reservoir In “Athran” Field South Sumatera Basin - Agustine, Diah Wully (Journal of Earth and Marine Technology (JEMT), 2020)
“Athran” field is an active field for hydrocarbon exploration with trending northeast-southwest and focus on the reservoir zone is the Talang Akar Formation with A-C layer intervals. The method used in this research is electrofacies, delta deposition system, formation evaluation, static reservoir modeling, and multi-attribute linear regression. The distribution of reservoir modeling is done by using the stochastic variogram method to make modeling lithofacies and depositional facies. Identification of lithofacies in the study area obtained two units, namely sandstone and shale facies. The depositional facies analysis was carried out using the electrofacies approach, showing that the research target was in a transitional environment with a delta deposition system, namely the distributary channel, delta front and prodelta. The deposition process. Sandstones and shales affect the distribution of porosity which functions as a reservoir property. The data integration of the distribution of lithofacies, gamma ray and porosity was carried out using the multi-attribute linear regression method to predict data both vertically and horizontally. The results of this study are used to help determine the distribution direction and direction of sediment deposition as a good reservoir zone for exploration activities.